An overview of solar still enhancement approaches for increased freshwater production rates from a thermal process perspective. (October 2021) - Mu, L.; Chen, L.; Lin, L.; Park, Y.H.; Wang, H.; Xu, P.; Kota, K.; Kuravi, S.
Abstract: With a growing population, lack of balance between water demand and traditional freshwater supply has become a critical issue. A solar still is a simple, impactful device for producing freshwater from alternative water sources such as brackish water, wastewater, and brine by sole or partial consumption of solar energy. Solar stills are highly suited for the water-stressed regions with limited access to electricity but abundant solar energy, or places with no sustainable and affordable options for clean water. Owing to these advantages, fundamental and applied research related to solar stills has been of interest to the water industry. The main shortcoming of solar stills is the low freshwater productivity, and thus the research focus in the field has been to improve their productivity. Existing review articles on solar stills presented their classification based mostly on the structural designs and add-ons for boosting the freshwater production rate. However, a solar still is fundamentally a system involving thermal processes. Therefore, this overview, for the first time, presents the classification of the solar stills from the perspective of the basic thermal processes involved and the associated enhancement techniques pursued for each of these processes. The advantage of this review is that it will enable to systematically understand the role and impact of each thermal process on the freshwater production rate, thereby enabling a pathway for the future researchers to focus on developing solutions from a perspective of reducing the largest thermal resistances. In addition, the present paper reviewed the recent developments in interfacial-evaporation-based enhancements for solar stills, which was not covered in the existing reviews. Highlights: Solar still enhancements are reviewed from a new perspective of thermal processes. Enhanced solar stills have potential to be competitive. Solar input followed by heat storage and evaporation processes impact productivity. Combination of enhancements was also found to improve productivity. Future enhancement needs are identified.